The Seven Wonders of the Ancient World - Jordan, Paul, 1941- (Routledge, 2014)
From the Pyramids at Giza to the Colossus of Rhodes, from the Hanging Gardens of Babylon to the Lighthouse of Alexandria, from the Temple of Ephesus to the Mausoleum at Halicarnassus and the Statue of Zeus at Olympia, the Seven Wonders of the Ancient World have never ceased to fascinate through the ages.